ADDRESSING THE NEW HAZARDS OF THE HIGH TECHNOLOGY WORKPLACE. (Harvard Law Review)
Explores how electronic performance monitoring and electronic mail interception are regulated by a system of free market and common law mechanisms that fail to protect workers from abusive practices in the absence of legislative solutions. Description of the phenomena of computer crime, electronic performance monitoring and electronic mail interception and the legal framework in which they operate; Recommendations.